PELAKSANAAN PERATURAN BUPATI GIANYAR NOMOR 57 TAHUN 2018 TENTANG MANAJEMEN DAN REKAYASA LALU LINTAS DAN ANGKUTAN JALAN SERTA PERPARKIRAN DI KAWASAN PARIWISATA UBUD - Tanaya, Putu Edgar; Sarif, Asri (Fakultas Hukum Universitas Ngurah Rai, 2023)
Along with the rapid development in the Ubud area, it must also be balanced with the developmentof accessibility that can support tourist comfort. Efforts made by the government such as providing centralparking and taking strict action against violators who still use the road as a parking lot in the Ubud tourismarea have also not been able to overcome this problem. The problems discussed in this study, namely: howis the gianyar district regulation number 57 of 2018 regarding management and engineering of traffic androad transportation and parking in the ubud tourism area and what are the inhibiting factors and effortsmade in the implementation of the gianyar district regulation number 57 of 2018 regarding managementand engineering of traffic and road transportation as well as parking in the tourism area of ubud. Theresearch used in this study is based on empirical juridical research which is also known as field research.The results of the research are that the implementation of the Gianyar Regional Regulation Number 57 of2018 has not gone well due to the many parking problems and the lack of parking facilities in the Ubudarea. Factors that influence the implementation of the Perbup are internal and external factors as well asthe efforts made by dividing the personnel of the Transportation Agency in Gianyar at several points in theUbud area. The suggestion submitted was the need for firmness from the Perbup implementing agency andvillage officials in the Ubud tourism area to help regulate parking.